III Early child growth and development: similarities across populations; differences across phenotypes and exposotypes. (18th March 2022) - Villar, J; Fernandes, M; Winsey, A; Villar de Onis, J; Papageorghiou, AT; Kennedy, S; ,
Abstract : The INTERGROWTH-21st Project has primarily addressed: 1) whether the variability in skeletal growth and early child development (ECD) within a population is larger than that among populations when health and nutritional needs are met, and 2) whether phenotypes and exposotypes of fetal and newborn growth are associated with differential growth and development during early childhood. Between 2009 and 2016, we first conducted serial standardised measurements of fetal and postnatal growth, and a standardised, comprehensive 24-months ECD assessment, in 4607 mothers and their infants from geographically delimited populations in Brazil, China, India, Kenya, Oman, the UK, and USA, that had low-risk indicators for perinatal and postnatal morbidity and mortality at population and individual levels. This allowed the construction of the first international standards of: (1) fetal growth (n=4321 fetuses from all participating sites) and (2) ECD, as measured on the INTER-NDA test at age 2 (n=1181 infants from five of the participating sites). The cohort's prescriptive nature was confirmed at age 2 years by demonstrating satisfactory postnatal growth and development, i.e. the infants overlapped at the 49th, 50th and 58th centiles for length, head circumference and weight, respectively, of the WHO Child Growth Standards, and between the 3rd and 97th centiles of the WHO motor development milestones. Using variance component analysis, the percentage of the total variance explained by among-site differences (as opposed to within-individuals in a population) ranged from 1.9% to 3.9% for skeletal growth (fetal, newborn and infant length) and 1.3% to 9.2% for neurocognitive outcomes measured on the INTER-NDA. 1 2 Secondly, the characterisation of phenotypes and exposotypes associated with differential early growth and development was examined in a cohort of 7311 preterm and term singleton newborns enrolled between 2012 and 2018 in maternity hospitals in Brazil, Kenya, Pakistan, South Africa, Thailand, and the UK. Using repeated ultrasound scans of fetal cranial growth measures from <14 weeks' gestation, five fetal trajectories were identified, subsequently associated with specific neurodevelopmental, behavioural, visual, postnatal morbidity and anthropometric measures at birth and at age 2 years (n=3598). Trajectories reflecting early faltering or accelerating fetal head circumference growth changed within a 20–25 week gestational age window and were associated with developmental scores at 2 years in a mirror (positive/negative) pattern, mostly focused on maturation of cognitive, language and visual skills. 3 Additionally, analysis of the 1381 preterm infants born within this cohort identified eight aetiologically-based preterm phenotypes, which were associated with markedly different neonatal morbidity, child growth and developmental profiles at age 2. These findings confirm that in early life: (1) within-population variability for skeletal growth and neurodevelopment is far greater than that among-populations when health and nutritional needs are met, and (2) epidemiological patterns between un-selected populations are largely environment-driven, expressed by phenotypes and exposotypes with differential risk profiles. The Project has also constructed, for the first time, a set of international standards to monitor human growth and development from early pregnancy to age 2, to facilitate unified clinical care and research (https://intergrowth21.tghn.org/standards-tools/). References: Villar J, Papageorghiou AT, Pang R, et al . The likeness of fetal growth and newborn size across non-isolated populations in the INTERGROWTH-21st project: the fetal growth longitudinal study and newborn cross-sectional study. Lancet Diabetes & Endocrinology 2014 Oct 1;2 (10):781–92. Villar J, Fernandes M, Purwar M, et al. Neurodevelopmental milestones and associated behaviours are similar among healthy children across diverse geographical locations. Nature Communications 2019 Jan 30;10 (1):1–0. Villar J, Gunier RB, Tshivuila-Matala CO, et al. Fetal cranial growth trajectories are associated with growth and neurodevelopment at 2 years of age: INTERBIO-21st fetal study. Nature Medicine 2021 Apr;27 (4):647–52.